Polite addressing and its linguistic representation - Болотникова, Алла Петрівна; Гунченко, Юлія Вікторівна; Чередник, Людмила Анатоліївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The article analyses interpretation of the category of addressee in the scientific literature, presents the specifics of the linguistic representation of polite addressee in the Ukrainian language. The features of the category of addressee and its linguistic representation from the point of sociolinguistic criteria view are described. Polite addressing is considered as a set of special linguistic indicators that represent communicative interaction, a certain instrument of influencing the addressee, which are sometimes more effective than communication itself. In addition, the emphasis is made on sociolinguistic, national and cultural features of the category of addressees. Polite addressee is regarded as a certain pragmatic vector that determines and regulates the strategy of the speaker's communicative behaviour, influencing the choice and use of language indicators, the specifics of linguistic means of expressing polite addressee use. Linguistic indicators of polite addressee, which are used by the speaker in order to establish a successful communicative act are highlighted and described. The category of addressee is not limited to implementation within one part of speech, since the addressee expressiveness is concentrated in pronouns, nouns and verbs that can name or indicate the addressee, thus the category of addressee is a cross-cutting category inherent not only to one part of speech. The main specialized grammatical indicators of polite addressee expression in the Ukrainian language are personal pronouns ти, Ви, addressee-personal verb forms, vocative case of nouns, imperative verbs, words of the addressee category (vocative and addressee intensifiers dear, respected, etc.), in which the addressee is lexicalized function. From the point of polite addressing view, speakers use a number of linguistic indicators that perform an appellative, phatic, regulatory, connotative, national-cultural function, pragmatically loaded and modally labelled to represent relationships. The authors claim that functional load of a polite addressee is to prepare the conditions for successful implementation of a communicative act. The semantics of the addressee is determined by speech contact, relationship between the communicants, communication situation and the speaker's intention.